Brassica carinata as an off-season crop in the southeastern USA: Determining optimum sowing dates based on climate risks and potential effects on summer crop yield. (February 2022) - Nóia Júnior, Rogério de Souza; Fraisse, Clyde W.; Bashyal, Mahesh; Mulvaney, Michael J.; Seepaul, Ramdeo; Zientarski Karrei, Mauricio A.; Iboyi, Joseph Enye; Perondi, Daniel; Cerbaro, Vinicius Andrei; Boote, Kenneth J.
Abstract: CONTEXT: Brassica carinata is usually grown in a double-cropping system with cotton and peanut in southeastern USA. One challenge related to this system is to define the best sowing dates to minimize the climatic risk and improve the chances for increased farmers' profitability. OBJECTIVE: The objective was to determine the best sowing dates for carinata-cotton and carinata-peanut double-cropping systems in different locations of the southeastern USA. METHODS: A calibrated crop simulation DSSAT model was used to simulate carinata life cycle and cotton and peanut yields for 9 locations in 4 states, with carinata sowing dates ranging from early September to March using 38 years of weather data (1981–2018), assuming that cotton and peanut sowing occurred immediately after the carinata harvest. RESULTS AND CONCLUSIONS: Results indicated that the optimal sowing date varied according to location. For Shorter, AL, Midville, GA, and Florence, SC, the occurrence of extreme weather events during carinata cycle were minimized, and the summer crop yields were the highest when carinata was sown at the end of October. For Fairhope, AL, Jay, and Quincy, FL, results showed that carinata sowing must occur in early November to minimize the climatic risks of a double-cropping system. For Live Oak and Citra, FL, carinata sowing is recommended for mid- to late-November. Advancing carinata sowing to September resulted in an increased number of low temperature (LT) events during the carinata reproductive phase. The delay in carinata sowing to January or later exposed carinata crop to a larger number of High Temperature (HT), and considerably reduced the yield potential of the peanut and cotton summer crops. SIGNIFICANCE: Our results quantified the climatic risks to the off-season carinata crop itself and to the subsequent summer crop, contributing to the sustainable expansion and commercial production of carinata in the southeastern USA. Graphical abstract: Unlabelled Image Highlights: Double cropping system with carinata and summer crops could promote biofuel production in USA, but present climatic risks. Optimal sowing date could minimize the occurrence of frost, droughts, heat and heavy rainfall events during carinata cycle. Carinata sowing should occur between late October and November to maximize the yield of summer crops. Reduced climate risk is key to the sustainable expansion and commercial production of carinata in the southeastern USA.